Innovative Rectal Suspension of Mesalamine Utilizing Mesoporous Silica for Sustained and Colon-Specific Drug Delivery : Novel rectal suspension of mesalamine - Prajapati, Rajnish Umesh; Bicchali, Usha; Bhattacharyya, Sayani (Iranian Journal of Pharmaceutical Sciences, 2025)
Mesalamine is an anti-inflammatory drug for the treatment of ulcerative colitis-related colon cancer. The present study aims to evaluate the rectal suspension of mesoporous mesalamine for improved localized effect of the drug in the ulcerative colon of rodents. Syloid 244FP and Syloid XDP were employed to form a solid dispersion of mesalamine using the solvent evaporation technique, with a drug-to-carrier ratio of 1:1. The formulations were evaluated for drug loading, and an in vitro drug release study was conducted over 8 hours. The drug and excipients were subjected to studies on incompatibility, surface characteristics, and surface morphology. A reconstitutable suspension (9% w/w) was prepared using carbomer 934 and Xanthum gum as suspending agents. Ulceration was induced in the animals, and the effect of the formulations on the ulcerative colon was observed through a histopathological study. The FTIR study revealed the compatibility between the drug and the carriers, while surface morphology and surface characteristics studies revealed the amorphization of the drug. Syloid 244FP was found to be the best carrier in terms of loading mesalamine and releasing the drug in a sustained manner for 8 hours. The histopathological study revealed that prolonged localization of the drug could provide significant healing in the ulcerative colons of the animals. Therefore, it can be concluded that the sustained release solid dispersion of mesalamine in mesoporous silica could enhance the local activity of mesalamine in the treatment of ulcerative colitis.